(untitled) (Bangladesh Journal of Animal Science, 2013)
A study was conducted to assess the impact of the distance education courses on dairy and goat farming on knowledge gained, skills obtained and economic benefits attained by the learners. The data was collected from 100 respondents who were selected randomly from 221 successful candidates during the period of 2000-01 to 2004-05. A majority of the respondents gained knowledge in credit/ insurance, housing systems followed by farm economics, clean milk production, calf rearing and feed and feeding methods. The respondents of all categories had increased their farm size (with percentage gain ranged between 59.38 and 75.07) and daily average milk yield (with percentage gain ranged between 48.34 and 66.17). Further the small, medium and large category farmers had gained additional income with per cent gain ranged from 73.38 to 122.26. There was a highly significant gain in production and income in all categories of farmers with respect to farm size, milk yield, sale of milk, dung and animals and net change in the value of stock. DOI: http://dx.doi.org/10.3329/bjas.v41i2.14133 Bang. J. Anim. Sci. 2012. 40 (2): 136-140